Development of motivation as a condition of organization of cognitive activity of students of higher educational institutions in the process of teaching the humanities (Pedagogy of Higher and Secondary Education, 2012)
Gushko O.A. Development of motivation as a condition of organization of cognitive activity of students of higher educational institutions in the process of teaching the humanities.The author of the article investigates the process of development of motivational sphere of students and distinguishes it as an objective condition of the organization of cognitive activity of students of higher educational establishments.
Keywords: organization of cognitive activity of students; motivation; cognitive motivation; forming of motivation; development of motivation